2020
DOI: 10.1002/acp.3745
|View full text |Cite
|
Sign up to set email alerts
|

Cellphone addiction explains how cellphones impair learning for lecture materials

Abstract: Students' cellphone use has been related to poorer learning, possibly due to greater distraction. This study investigated whether cellphone-related anxiety, addiction, and disconnection were related to distraction and learning as well as how practical educational policies could minimize negative effects. Participants (N = 218) watched a video lecture and were divided into two groups: cellphone-allowed for academic use (Use-Cellphone Group) and no cellphone instruction (No-Instruction Group). During the lecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Hence, individuals do not seem to invest cognitive efforts in developing knowledge about the system but become increasingly complacent in blindly adhering to what the system says. This observation accords with previous studies reporting declining cognitive efforts of people who can constantly rely on technological support (Mendoza 2018;Lee et al 2021). Sparrow (2011), for instance, coined the term "Google effect" after investigating the recall of words people typed into a computer.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, individuals do not seem to invest cognitive efforts in developing knowledge about the system but become increasingly complacent in blindly adhering to what the system says. This observation accords with previous studies reporting declining cognitive efforts of people who can constantly rely on technological support (Mendoza 2018;Lee et al 2021). Sparrow (2011), for instance, coined the term "Google effect" after investigating the recall of words people typed into a computer.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Dietz and Henrich (2014) asked participants to watch a prerecorded lecture, and those who texted on a smartphone during the lecture performed worse on a follow-up quiz. Similar findings have emerged in college classrooms (Froese et al, 2012;Lee et al, 2021;Mendoza et al, 2018), although others have found students can tolerate low to moderate texting with performance only being disrupted in heavy texters (Rosen et al, 2011).…”
Section: Media Multitaskingsupporting
confidence: 69%
“…For example, 51% of college students report feeling anxious if they cannot check their device as often as they would like (Rosen et al, 2013), and high smartphone users report feeling anxious when their smartphone is taken away (Cheever et al, 2014). Others have found those with greater levels of smartphone addiction are prone to disruptive internal interference triggered by text notifications (Lee et al, 2021). Thus, the smartphone serves as a source of internal interference, but more research is warranted.…”
Section: Internal Interference Anxiety and Smartphonesmentioning
confidence: 99%
“…Common Sense Media reported in 2015 that teens use media an average of nine hours a day, and Pew Research asserted that up to 45% of teenagers are online "on a near constant basis" . Research has demonstrated that students who are allowed cell phones are distracted even by receiving notifications alone (Lee et al, 2021), and even the presence of a cellphone can be distracting (Ward et al, 2017).…”
Section: Problemmentioning
confidence: 99%
“…It's not a solution, and device distraction is an issue in high school as well as in the college classroom , and divided attention in the classroom has been shown to reduce exam performance and impaired long-term retention of teacher lessons . Students with frequent software multitasking on laptops exhibit lower academic performance than students with a low frequency of software multitasking (Kraushaar & Novak, 2010;Lee et al, 2021). Trying to accomplish two thinking tasks simultaneously cannot be done.…”
Section: Problemmentioning
confidence: 99%